Pseudolycorine N-oxide, a new N-oxide from Narcissus tazetta. Issue 14 (17th July 2020) - Katoch, Deepali; Kumar, Dharmesh; Padwad, Yogendra S.; Singh, Bikram; Sharma, Upendra
Abstract: A new N -oxide, Pseudolycorine N -oxide (1 ) was characterised along with eleven known alkaloids homolycorine (2 ), O -methylmaritidine (3 ), 8- O -demethylhomolycorine (4 ), homolycorine N -oxide (5 ), lycorine (6), narciclasine (7 ), pseudolycorine (8 ), ungeremine (9 ), 8- O -demethylmaritidine (10 ), zefbetaine (11 ) and lycorine N -oxide (12 ), from Narcissus tazetta . Their structures were established on the basis of spectroscopic data analysis. The extract, fractions and isolated compounds were screened for in vitro cytotoxicity against two human cancer cell lines, human cervical cancer (SiHa) and human epidermoid carcinoma (KB) cells. The study demonstrated the cytotoxic potential of extract and its chloroform and n -butanol fractions. Further, the results revealed the bioactive potential of narciclasine, pseudolycorine and homolycorine alkaloids. However, new N -oxide (1 ) was not active against these cell lines. Graphical Abstract: